2012
DOI: 10.1128/jb.06297-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Mycoplasma iowae Strain 695, an Unusual Pathogen Causing Deaths in Turkeys

Abstract: Mycoplasma iowae is associated mainly with reduced hatchability in turkeys and is well known for the unusual ability of phenotypic variation in the Mycoplasma surface components as well as a relative resistance to heat, bile salts, and many antimicrobials. A subset of unique genes and a gene cluster responsible for these characteristics could be identified from the genome. Here, we report the first genome sequence of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…These M. iowae homologues have 28% and 25% identity, respectively, to the M. pneumoniae CARDS toxin sequence. Each M. iowae gene also has 99% identity to its respective homolog in M. iowae serovar I strain 695 [ 50 ]. cards1 was chosen despite the greater degree of disparity from M. pneumoniae CARDS toxin since only 20 bases separate cards1 and cards2 , likely making both genes transcriptionally linked.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These M. iowae homologues have 28% and 25% identity, respectively, to the M. pneumoniae CARDS toxin sequence. Each M. iowae gene also has 99% identity to its respective homolog in M. iowae serovar I strain 695 [ 50 ]. cards1 was chosen despite the greater degree of disparity from M. pneumoniae CARDS toxin since only 20 bases separate cards1 and cards2 , likely making both genes transcriptionally linked.…”
Section: Resultsmentioning
confidence: 99%
“…Both genome sequences currently available for M. iowae [ 13 , 50 ] reveal the presence of a gene for catalase, an H 2 O 2 -degrading enzyme absent from all other published mycoplasma genomes, which produces an active protein [ 13 ]. Bacteria can encounter exposure to H 2 O 2 from a variety of different sources, including other bacterial pathogens as well as the host immune response [ 1 , 2 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the reference strains, it could detect between 1 and 5 pg of M. iowae DNA, which approximately corresponded to between 0.2 and 2.99 CFUs per ml ( Table 2). The complete genome sequence of M. iowae has been published recently (Wei et al, 2012) and reveals the presence of two rRNA operons, which may help to explain why the sensitivity can be less than one organism per reaction. This detection limit is similar to that obtained by Lierz et al (2008) who detected as little as 0.1 CFU, and is lower than the 3.2 CFUs per PCR reaction found by Cai et al (2008) or the 10 colour changing units per reaction reported by Laigret et al (1996).…”
Section: Discussionmentioning
confidence: 99%
“…in preventing disease and enhancing sh growth [97], [101], however the underlying molecular mechanism remains elusive and the absence of a complete genome sequence prevents the possibility to deduce the functional potential of this new Mycoplasma genus. Similarly, it is also di cult to infer potential functions of the newly discovered Mycoplasma genus relying on its closest relatives with sequenced genomes, as these are the well-known mammalian pathogens M. penetrans [104] (16S rRNA gene V3-V4 region sequence similarity of 93.26%) and M. iowae[105] (16S rRNA gene V3-V4 region sequence similarity of 91.20%). Whether this Mycoplasma genus is capable of conferring some degree of protection from pathogenic infections or enhance sh growth needs further investigations.…”
mentioning
confidence: 99%